2015
DOI: 10.1007/s00228-015-1873-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacokinetics of melatonin: a systematic review

Abstract: Despite methodological differences between the included studies, Tmax was approximately 50 min following oral immediate-release formulations of melatonin. T1/2 was 45 min in both administration routes. Cmax, AUC, Cl, and VD varied extensively between studies. Bioavailability of oral melatonin was approximately 15%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
164
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(202 citation statements)
references
References 34 publications
10
164
0
5
Order By: Relevance
“…It is achievable for 20 mM melatonin clinically [58]. Moreover, a systematic review article also concluded that time to maximal plasma/serum concentration (Tmax) was approximately 50 min following oral immediate-release formulations of melatonin and the bioavailability of oral melatonin was approximately 15% [59]. Thus, the experimental concentrations of Melatonin used in this study (0–1 mM) could become clinically achievable.…”
Section: Discussionmentioning
confidence: 97%
“…It is achievable for 20 mM melatonin clinically [58]. Moreover, a systematic review article also concluded that time to maximal plasma/serum concentration (Tmax) was approximately 50 min following oral immediate-release formulations of melatonin and the bioavailability of oral melatonin was approximately 15% [59]. Thus, the experimental concentrations of Melatonin used in this study (0–1 mM) could become clinically achievable.…”
Section: Discussionmentioning
confidence: 97%
“…Some authors believed that there could be a carry-on effect of melatonin on sleep parameters and circadian rhythm 15 28 30. A recent systematic review on the pharmacokinetics of melatonin showed that the maximum concentration of melatonin after supplementation would be reached after approximately 50 min with oral immediate-release formulations 30. The elimination half-life of both oral and intravenous melatonin was about 45 min.…”
Section: Discussionmentioning
confidence: 99%
“…The dogs adopted by Wang et al [25] were younger and lighter. It has been known that the clinical pharmacokinetics of exogenous MEL was affected by age [17]; therefore, we speculated that the difference in the dog pharmacokinetics of MEL might be caused by the same reason.…”
Section: Pharmacokinetic Studymentioning
confidence: 94%
“…The pharmacokinetics of exogenous MEL in rat, dog and human have been investigated [13][14][15][16][17]. Nevertheless, there is little information about the pharmacokinetics of its major metabolites 6-O-MEL and S-O-MEL, which is partly due to lack of convenient analysis methods for simultaneous quantification of MEL and its metabolites in bio-matrices.…”
Section: Introductionmentioning
confidence: 99%